Evaluasi Penggunaan Regimen Proton Pump Inhibitor (PPI) Terhadap Outcome Klinis Pada Pasien Gastritis Rawat Jalan Di RSUD X - aida_ayu maharani; Endang Setyowati; Fahrudin Arif (JURNAL FARMASI DAN MAKANAN, 2026)
Gastritis is an inflammation of the gastric mucosa with Proton Pump Inhibitors (PPIs) as the first line of treatment. This study aims to evaluate PPI regimen use and its relationship with treatment success in outpatients with gastritis. The study design is an observational analytical study with a retrospective approach. The sample in this study consisted of 107 patients, namely outpatients diagnosed with gastritis who used PPIs from January 2024 to December 2025. The data were analyzed univariately to describe the characteristics of the variables in frequency distribution and percentage. The results showed that most patients were in the 46-70 age range (46.7%) and were female (76.6%). The most common level of education was high school (37.4%), and the majority of patients were unemployed (63.6%). A total of 58.9% of patients had comorbidities, with hypertension (13.1%) and diabetes mellitus (11.2%) being the most common comorbidities. The pattern of therapy use shows that the combination of lansoprazole and sucralfate was the most commonly used regimen (48.6%). The most commonly prescribed drug was lansoprazole, with 78 uses (41.3%). The evaluation of treatment outcomes showed that 78.5% of patients were declared successful, with 55.1% of patients not returning for follow-up visits, 97.2% not requiring escalation of treatment, and no patients requiring hospitalization.